(untitled) (Bangladesh Journal of Pharmacology, 2011)
The antibacterial effects of three mushrooms extract Ganoderma lucidum, Auricularia auricula, Pleurotus florida were studied against Staphylococcus aureus and Escherichia coli. A. auricula showed significant antibacterial activity against S. aureus. P. florida showed some antibacterial activity while G. lucidum showed no antibacterial activity. None of the extracts showed any activity against E. coli.